Plea Bargaining dalam Sistem Peradilan Pidana di Beberapa Negara - Nella Octaviany Siregar (Wajah Hukum, 2019)
Plea Bargaining System is widely interpreted as a statement of guilt of a suspect or defendant. Plea Bargaining practised in many countries that have embraced the Common Law legal system. Plea Bargaining that was developed in the common law "legal system" has inspired the emergence of "mediation" in the practice of the judiciary based on the criminal law in the Netherlands and France, known as "transactie". Plea Bargaining is categorized as a settling outside the hearing and their users is also based on specific reasons. Even in the renewal of law criminal justice events in Indonesia, has also picked up the basic concept of plea bargaining that was adopted in the RUU KUHAP with the concept of "Jalur Khusus". That with the presence of the concept of "Jalur Khusus", is also a concern when viewed can enactment back recognition of guilt of the defendant as the basis of the judge's verdict is dropping. The purpose of this paper is to find out, analyze the plea bargaining in some countries. The type of research used is the juridical normative research, using a conceptual approach, comparative approach, historical approach.